Nurses experiences and views in caring for prisoner-patients in a secondary care environment - Turner, Claire (2012)
Background It is recognised that prisoners suffer varying health problems on initial imprisonment and are at risk from a range of health problems over their sentence duration. These health problems are contributing to the increased prevalence of prisoners in secondary care, last recorded as annually 47,857. Research currently fails to address the topic of nurses’ experiences and views of caring for prisoners in secondary care. The aim of this study was to gain knowledge of nurses’ experiences and views in caring for prisoners in general hospitals, and disseminate this acquired information to Eastside Trust. Initially it was required, in line with the objectives, to identify stigma and social exclusion in care of prisoner-patients and any consequential impacts on healthcare. The review of the literature also incorporated examination of professional issues and current guidance available, which revealed levels of support to be insufficient especially considering the growing number of prisoner-patients requiring secondary care. Methodology A quantitative methodology was selected with qualitative elements. Development of a questionnaire amended from Browne et al’s (2006) study lead to exploration of 244 nurses’ views and experiences about guidance, practices, confidentiality and equality of care. Responses were inputted to generate descriptive and inferential statistics. Open-ended questions received thematic analysis. Findings Exploration revealed that 75% of nurses had cared for prisoner-patients in the previous five years, whilst only 21.3% were aware of guidelines. The findings from this service evaluation display diversity in nursing practices in caring for prisoner-patients in general hospitals. Of nurses who had cared for prisoners: 45.4% had felt uncomfortable during care; 60.7% never asked prison officers to leave; 47.5% never asked if the prisoner-patient was a risk to their safety; and 44.8% had always cared for prisoner-patients whilst restrained. When examining perceptions of confidentiality in care, 43.4% perceived there to be breaches in confidentiality, which of these 59.4% perceived breaches to be justified. Lastly, a third of respondents expressed that they perceived there to be inequality between prisoner-patients and non-prisoner patients. Numerous views were voiced as reasoning for feeling uncomfortable providing prisoner-patient care. Variables, such as lower levels of interaction, prejudices exhibited by staff and patients, presence of handcuffs and prison officers and staff uncertainty were identified as barriers to equality. Discussion It is considered that although there is the indication that prisoner-patients could be receiving care evaluated as not complying with guidelines due to prisoner status, that this could be reversed, therefore they receive preferential treatment to achieve hasten discharge. Recommendations for practice improvement have been made which will involve dissemination of findings to the Trust. Undertaking care of prisoners is complex requiring professional, moral, and ethical understanding. However, it remains that acting in prisoner-patients’ best interests and providing exceptional care, confidentiality and dignity, equivalent to that of non-prisoner patients must prevail.